ANALISIS TINGKAT PARTISIPASI WANITA DALAM ANGKATAN KERJA DI JAWA TENGAH PERIODE TAHUN 1982-2000 - Eni Setyowati (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2009)
At industrialization phase, women will be shifted by men because the increasing of unemployment. When economic development reaches a certain stage, the trend of development turned with increasing women employment. Purpose of the research that will be reached is to estimate influence of women unemployment, women resident that managing household, and women residents that still school on the level of women participation in the labor force in Central Java (1982-2000). This study clarifies the factors that influence the level of participation of women in the labor force and improve the existence theory of the labor force participation rate. One way to analyze the effect of short-run and long run is to use a dynamic model. In this research model used is the Engle Granger Error Correction Models (EG-ECM) which based on "granger representation theorem". The result knows the variable having influence which significance in short-run are women resident that managing household and women resident that still school.